Disease burden of patients with pemphigus from a societal perspective. (2nd January 2021) - Brodszky, V.; Tamási, B.; Hajdu, K.; Péntek, M.; Szegedi, A.; Sárdy, M.; Bata-Csörgő, Z.; Kinyó, Á.; Gulácsi, L.; Rencz, F.
ABSTRACT: Introduction : Cost-of-illness studies are widely used for healthcare decision-making; however, no such study is available in pemphigus from the societal perspective. The purpose of this analysis was to estimate annual cost-of-illness per patient with pemphigus from a societal perspective. Areas covered : Between 2014 and 2017, a multicenter, cross-sectional study was carried out. Consecutive pemphigus patients aged ≥18 years were recruited at all four university dermatology departments in Hungary. Direct and indirect costs were calculated, including costs for treatments, outpatient visits, hospital admissions, informal care, travel costs and productivity loss. Generalized linear model was used to analyze predictors of costs. Atotal of 109 patients with pemphigus enrolled with amean age of 57.1 (SD 14.8) years. Total cost per pemphigus patient was €3, 995 (SD €7, 526) peryear, with productivity loss (58%) and informal care (19%) accounting for the majority. Annual means of 189 and 41 working hours were lost due to absence from work and reduced productivity, respectively. Younger age and pemphigus vulgaris were associated with higher costs (p < 0.05). Expert opinion : This is the first cost-of-illness study applying the societal perspective in pemphigus. Our results indicate a substantial economic burden on society, mainly driven by productivity loss and informal care.